Exhaled nitric oxide production by nitric oxide synthase-deficient mice - Steudel, Wolfgang; Kirmse, Max; Weimann, Jörg; Ullrich, Roman; Hromi, Jonathan; Zapol, Warren M. (American journal of respiratory and critical care medicine, 2000)
Nitric oxide (NO) is produced in the nasal cavities, airways, and lungs and is exhaled by normal animals and humans. Although increased exhaled NO concentrations in airway inflammation have been associated with increased airway expression of nitric oxide synthase 2 (NOS 2), it is uncertain which NOS isoform is responsible for baseline levels of exhaled NO. We therefore studied wild-type mice and mice with a congenital deficiency of NOS 1, NOS 2, or NOS 3. By studying a closed chamber in which the exhaled gas of a group of mice was collected, gaseous NO production rates were measured. Wild-type mice exhaled 362 ± 35 × 10− 15 mol g− 1 min− 1 NO (mean ± SE, n = 16 groups of five mice), NOS 1-deficient mice exhaled 592 ± 74 × 10− 15 mol g− 1 min− 1 NO (n = 15 groups, p < 0.05 versus wild-type and NOS 2-deficient mice), NOS 2-deficient mice 330 ± 74 × 10− 15 mol g− 1 min− 1 NO (n = 14 groups) and NOS 3-deficient mice 766 ± 101 × 10− 15 mol g− 1 min− 1 NO (n = 16 groups, p < 0.001 versus wild-type and NOS 2-deficient mice). Pharmacological NOS inhibition with l-NAME decreased (p < 0.05) the exhaled NO production rate of wild-type and NOS 3-deficient but not of NOS 2-deficient mice. l-Arginine administration increased exhaled NO production rate in all but NOS 2-deficient mice. Absence of NOS 1 or 3 is associated with increased murine exhaled NO production rates. Since NOS 2-deficient mice were the only genotype to lack substrate- and inhibitor-regulated changes of NO exhalation, we suggest that NOS 2 is an important isoform contributing to exhaled NO exhalation in healthy mice.
Gesehen am 10.01.2022